Prevalence Estimates of Antibodies Towards Foot-and-Mouth Disease Virus in Small Ruminants in Uganda - Balinda, S. N.; Tjørnehøj, K.; Muwanika, V. B.; Mwiine, F. N.; Ayebazibwe, C.; Masembe, C.; Siegismund, H. R.; Alexandersen, S. (Transboundary and emerging diseases, 2009)
Foot-and-mouth disease (FMD) is endemic in Uganda with control strategies focusing on vaccination of cattle, while small ruminants are largely ignored. In order for Uganda to establish effective control strategies, it is crucial that the epidemiology of the disease is fully understood. This study summarizes results of serological investigations of sheep and goats for antibodies to FMDV from four districts in 2006 following an FMD outbreak in the region and from an attempted comprehensive random sampling in two districts in 2007. Antibodies were quantified and serotyped using competitive ELISA for antibodies towards non-structural proteins (NSP) and structural proteins towards serotype O, and blocking ELISA for antibodies towards the seven serotypes of FMD virus (FMDV). In 2006, sheep and goats in Bushenyi and Isingiro districts were free from antibodies towards FMDV, while herds in Kasese and Mbarara districts excluding Kahendero village were all positive for antibodies towards NSP and SP-O. In 2007, mean prevalence estimates of antibodies towards FMDV NSP was 14% in goats and 22% in sheep in Kasese district, while Bushenyi was still free. The difference between these two districts probably reflects different levels of FMDV challenge attributed to the variation in exposure rates which again in part may be as a result of the differing husbandry practices. Contrary to 2006, with clear antibodies towards serotype O, the serotype-specificity of the antibodies was less clear in 2007, as antibodies towards both serotype O and SAT serotypes were identified. Our results show that goats and sheep are infected during FMD outbreaks, and that they may be useful for determining the serotype of FMD outbreaks in Uganda, if they are sampled shortly after an outbreak.
Keywords: foot-and-mouth disease virus; small ruminants; antibodies; husbandry practice